Luther's Heidelberg Disputation and identity formation. Issue 1 (4th March 2019) - Bräutigam, Michael
Abstract: Luther's famous Ninety‐five Theses overshadowed his twenty‐eight theses of the Heidelberg Disputation . This is regrettable insofar as Luther broke in Heidelberg with the traditional scholastic method and introduced for the first time publicly his influential theology of the cross. Luther's existential emphasis in this Disputation is particularly significant, because he answers here the big questions for us: Who am I really in the sight of God? What is my true identity in Christ? Luther radically exposes our self‐centeredness and calls us to look at the world, God, and ourselves through "suffering and the cross, " as only in this way will we be able to perceive clearly and "say what a thing is." He encourages us to become theologians of the cross who have given up on themselves and discovered that "everything is already done." Luther's passionate plea to put the cross of Christ at the center of our lives is a welcome reminder for us today, even five hundred years later, as we seek to find out who we are, who God is, and what God is accomplishing in and through us. Rescuing Luther's Heidelberg Disputation from oblivion is vital for the health of both church and academia today.